An Analysis of Grice's Maxims in Finding Nemo and Finding Dory Movies - Anak Agung Megantari Putri; I Gusti Agung Istri Aryani; I Nyoman Arya Wibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study explores the application and violation of Grice's conversational maxims in the animated films